Piezoelectric relaxation of two-dimentional electron gas in InGaN/GaN heterostructures with quantum wells - Evgeny R. Burmistrov; Lev P. Avakyants; Marina M. Afanasova (SN Applied Sciences, 2021)
Abstract The article is devoted to the study of the mechanism of piezoelectric scattering of charge carriers in an InGaN/AlGaN/ GaN heterostructures with one filled quantum-confinement subband. The aim of the article is to create a mathematical model that can be used to estimate the kinetic parameters of a two-dimensional electron gas (2DEG) in the structure under study. The results of the calculation of the matrix scattering potentials demonstrated the reliability and consistency on the used model of industrial LED heterostructures with InGaN/GaN quantum wells. It is shown that mechanical stresses in the InGaN/GaN layers lead to an uneven distribution of the total electric field along the active layer. It has been established that the lifetime limiting the mobility of a two-dimensional electron gas in piezoelectric scattering is of the order of 10–9 s.